The influence of modernization of tax administration and organizational culture on tax revenues through taxpayer motivation - Nurhidayah; Wahyuddin S; Zul Rachmat; Amriadi (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2023)
This study aims to find out and describe the Influence of the Modernization of Tax Administration and Organizational Culture on Tax Revenue through Taxpayer Motivation at the Samsat Office of Wajo Regency. This is quantitative research. The population was motor vehicle taxpayers registered in The Wajo Regency Samsat in 2020. The sampling method employed the Slovin formula to determine the minimum number of samples from a limited population. In this study, we involved 100 respondents. Partial Least Square (PLS) Analysis technique assisted by SmartPLS 3.0 program was used to analyze data. We found that the Modernization of Tax Administration has a positive and insignificant effect on tax revenue, the Organizational Culture variable has a positive and significant effect on Tax Revenue, the Taxpayer Motivation variable has a positive and significant effect on Tax Revenue, the Tax Administration Modernization variable has a positive and significant effect on Tax Revenue through Taxpayer Motivation. The organization's culture positively and significantly affects Tax Revenue through Taxpayer Motivation.